2001
DOI: 10.1063/1.1359444
|View full text |Cite
|
Sign up to set email alerts
|

Reflected shock experiments on the equation-of-state properties of liquid deuterium at 100–600 GPa (1–6 Mbar)

Abstract: Laser-driven shock experiments are used to study the equation-of-state (EOS) properties of liquid deuterium. Reflected shocks are utilized to increase the shock pressure, to expand the area of EOS phase space probed by the experiment, and to enhance the sensitivity to differences in compressibility. The results of these experiments differ substantially from the predictions of the Sesame EOS. EOS models showing large dissociation effects and large compressibility (up to a factor of 2) agree with the data. By us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Ab initio methods predict a secondary shock pressure about 25% lower than measured experimentally. This is outside of the experimental error bars reported in [21] (which have increased compared to [9]). Only for u s1 = 25 km s −1 is agreement found.…”
contrasting
confidence: 58%
“…Ab initio methods predict a secondary shock pressure about 25% lower than measured experimentally. This is outside of the experimental error bars reported in [21] (which have increased compared to [9]). Only for u s1 = 25 km s −1 is agreement found.…”
contrasting
confidence: 58%
“…Although early laser-driven double shock measurements on the Nike laser 42,43 using an aluminum anvil appeared to be consistent with a soft EOS, subsequent higher precision double shock data obtained on the Omega laser 32 using a quartz anvil indicated a stiff EOS for first-shock pressures below ϳ100 GPa and above ϳ200 GPa, and an "intermediate" EOS suggestive of ϳ 5 in between. The Omega experiments provide a rigorous test of the deuterium compressibility ͑albeit in the double shock state͒ because the data are independent of models for the standard.…”
Section: B Previous Experimentsmentioning
confidence: 95%
“…This temperature is smaller than the Fermi temperature of the metallic fluid (∼ 16 eV), the samples are a degenerate metal. Improvement in compression (up to ∼ 12-fold) has been reported in reflected-shock experiments where the second shock occurs at ∼ 100GP a along the primary Hugoniot line (Mostovych et al, 2001(Mostovych et al, , 2000. Pressures up to 600 GPa were reported.…”
Section: Fig 11 (Color Online)mentioning
confidence: 82%
“…WPMD (gray right-triangle) (Knaup et al, 2003) 4.3 ± 0.1 also in disagreement with laser-driven shock experiments. In a subsequent study combining RPIMC (T>10 5 K) and first-principles MD (T<10 5 K) simulation techniques , the secondary Hugoniot was investigated and results compared with the experimental data of Mostovych et al (Mostovych et al, 2001(Mostovych et al, , 2000. Even in this case it was found that RPIMC and AIMD were in essential agreement but both at variance with the secondary Hugoniot from laser-driven experiments.…”
Section: Fig 11 (Color Online)mentioning
confidence: 87%